2014
DOI: 10.1039/c3cp54969k
|View full text |Cite
|
Sign up to set email alerts
|

Strain-assisted, low-temperature synthesis of high-performance thermoelectric materials

Abstract: Utilizing internal energy artificially implemented by cold-pressing in the specimens, we demonstrate a way to synthesize high-quality bulk thermoelectric materials at otherwise too low a temperature to approach to an equilibrium state. This low-temperature synthesis technique will provide a new opportunity to integrate high-performance thermoelectric materials into various electronic devices for a built-in energy source, as well as to develop low-cost fabrication methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…After the annealing process, the (0 0 l) texture orientation decreased, and the intensity of the main peak of (0 1 5) increased with the annealing temperature. Such a texture reorientation is attributed to the recrystallization process, releasing residual energy from cold pressing [39]. Jun et al observed the same recrystallization process at the annealing treatment when they applied strain energy to stoichiometric ingots (Bi 0.45 Sb 1.55 Te 3 ) by cold pressing (pressure at gigapascal scale) and then annealing at 300 • C in a vacuum [39].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…After the annealing process, the (0 0 l) texture orientation decreased, and the intensity of the main peak of (0 1 5) increased with the annealing temperature. Such a texture reorientation is attributed to the recrystallization process, releasing residual energy from cold pressing [39]. Jun et al observed the same recrystallization process at the annealing treatment when they applied strain energy to stoichiometric ingots (Bi 0.45 Sb 1.55 Te 3 ) by cold pressing (pressure at gigapascal scale) and then annealing at 300 • C in a vacuum [39].…”
Section: Resultsmentioning
confidence: 94%
“…Such a texture reorientation is attributed to the recrystallization process, releasing residual energy from cold pressing [39]. Jun et al observed the same recrystallization process at the annealing treatment when they applied strain energy to stoichiometric ingots (Bi 0.45 Sb 1.55 Te 3 ) by cold pressing (pressure at gigapascal scale) and then annealing at 300 • C in a vacuum [39]. The top view and FE-SEM images of the fractured surfaces of specimens prepared at RT, 300, 400, and 500 • C are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%